Protective effects of AER-271 in acute-phase radiation-induced brain injury in rats: reduction of brain edema, inflammation, apoptosis and maintenance of blood-brain barrier integrity - Xiong, Yaozu; Wang, Yifei; Li, Mingyue; Yu, Changhua; Tong, Yusuo; Xu, Xiaoting (Frontiers in Pharmacology, 2025)
ObjectiveThe expression changes of aquaporin-4 (AQP4) in radiation-induced brain jinjury (RIBI) and whether it is involved in the pathologic development of RIBI are currently unknown. In this study, we constructed a RIBI model by whole-brain radiation of Sprague-Dawley (SD) rats and tried to reveal the role of AQP4 in RIBI. The specific inhibitor AER-271 was used to inhibit the expression of AQP4 in RIBI to explore its neuro-protective effect.MethodsSD rats were randomly divided into Sham group and IR group. The trend and role of AQP4 in RIBI were explored by H&E staining, Western blot, brain tissue water content measurement, Evans blue (EB) osmolality assay, and immunofluorescence staining. Then SD rats were randomly divided into Sham group, AER-271 group, IR group and IR+AER-271 group to investigate the neuroprotective effects of AER-271 by H&E staining, Western blot, brain tissue water content measurement, EB osmolality assay, immunofluorescence staining, qRT-PCR and Elisa.ResultsRadiation promoted the expression of AQP4 in rat brain tissue, leading to its “depolarized” distribution. The expression level of AQP4 correlated with the severity of cerebral edema. Treatment with AER-271 reduced cerebral edema, attenuated inflammation and apoptosis, and maintained the integrity of the blood-brain barrier (BBB) in RIBI rats.ConclusionAQP4 is involved in regulating the subsequent inflammatory response, BBB injury and apoptosis by mediating the development of cerebral edema during the acute phase of RIBI. AER-271 is expected to be a promising therapeutic candidate for the treatment of RIBI by inhibiting the expression of AQP4.